Contribuições metodológicas para o ensino de matemática - Duarte, Raquel Coziuc (2020)
This work had as its theme the methodologies for teaching Mathematics, demonstrating how teachers can innovate their daily activities in the classroom. Examples of application are presented in the classroom from 2016 to 2019, in the seventh year of a State School, in the first years of Secondary Education in a second State School, in the sixth and seventh years of a Municipal School, and in the fourth and sixth years years of a second Municipal School, the first State School in the municipality of Bady Bassitt and the others in São José do Rio Preto. In the activities, in which concrete materials are presented, the components used to make them are shown, which can be manufactured by the students themselves in the classroom. Also, the concept of mediating evaluation is presented, very present in active methodologies. The results of this research showed that students are more interested in classes and participate more attentively, either by producing materials or presenting their work orally.